2010
DOI: 10.1111/j.1872-034x.2010.00703.x
|View full text |Cite
|
Sign up to set email alerts
|

New classification of dynamic computed tomography images predictive of malignant characteristics of hepatocellular carcinoma

Abstract: Heterogeneity of dynamic CT images correlates with malignant characteristics of HCC and can be potentially used to predict the malignant potential of HCC before treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
69
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 23 publications
8
69
0
Order By: Relevance
“…These results agree with those from previous studies in which peritumoral parenchymal enhancement or tumorous arterioportal shunt was associated with microvascular invasion (16,17,34). The rim enhancement pattern has been also suggested to indicate rapid progression, poor differentiation, and worse prognosis (22,25,35), possibly by reflecting the absence of a capsule, infiltrative growth, and the presence of microvascular invasion as well as rapid growth with central necrosis.…”
Section: Discussionsupporting
confidence: 83%
“…These results agree with those from previous studies in which peritumoral parenchymal enhancement or tumorous arterioportal shunt was associated with microvascular invasion (16,17,34). The rim enhancement pattern has been also suggested to indicate rapid progression, poor differentiation, and worse prognosis (22,25,35), possibly by reflecting the absence of a capsule, infiltrative growth, and the presence of microvascular invasion as well as rapid growth with central necrosis.…”
Section: Discussionsupporting
confidence: 83%
“…The diagnosis of HCC was established by histopathology or typical appearance of HCC on two sets of imaging studies (ultrasonography, computed tomography (CT), magnetic resonance imaging, or angiography) and/or based on elevation of tumor markers, such as α ‐fetoprotein (AFP) and DCP. We retrospectively evaluated and classified the vascular patterns of tumors in cases treated with RFA by imaging studies previously reported . Briefly, HCC was classified into four patterns, Type‐1,‐2,‐3, or‐4 according to pattern of enhancement.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, Type‐3 pattern represents a heterogeneous enhancement pattern with a septum‐like structure, which is associated with not only SN but also SN with extranodular growth type (SNEG) or confluent multinodular type (CMN). Type‐4 represents a heterogeneous enhancement pattern with irregular ring‐like structures, which was also associated with SN, SNEG, and CMN . The status of viral hepatitis infection was evaluated in all patients by the presence of serum anti‐HCV antibody and serum hepatitis B surface antigen.…”
Section: Methodsmentioning
confidence: 99%
“…If there are evident associations between IRE and prognostic histopathologic features, IRE could be used as an imaging biomarker for prognosis based on the associations. However, to the best of our knowledge, no comprehensive studies of the histopathologic features of IRE-HCCs exist, although some histopathologic findings observed in IRE-HCCs have been sporadically described [13][14][15]. Therefore, the purpose of this study was to examine the histopathologic characteristics of HCCs showing IRE in the arterial phase of gadoxetate-enhanced MRI, and compare them to HCCs without IRE.…”
Section: Introductionmentioning
confidence: 99%